Capsaicin determination in chilli fruit using a new solid-state sensor based on reflectance transduction - Mohammad R.; Arip M.N.M.; Ahmad M.; Heng L.Y.; Shafie K.A. (American Scientific Publishers, 2024)
Indexed by Scopus